Impact of Implementing Structured Compensatory Methods on Knowledge and Awareness of Cognitive Dysfunction Management Among Neurological Disorder Patients in Vijayapur Hospitals - Nelson Vijaykumar; Aleyamma Varghese (RGUHS Journal of Nursing Sciences)
Background Cognitive impairment hinders thinking learning memory and decision-making with symptoms like memory loss poor concentration and mood changes. It can result from neurotoxicity ischemia or neurodegenerative diseases like Alzheimerrsquos and Parkinsonrsquos.Objectives The study aimed to assess knowledge about cognitive impairment evaluate the effectiveness of structured compensatory techniques and analyze the relationship between knowledge scores and sociodemographic variables.Methodology The study assessed the effectiveness of structured compensatory techniques in improving knowledge about cognitive impairment among neurological patients in Vijayapura hospitals. A one-group pre-test post-test design was employed with participants being adults literate in Kannada or English and hospitalized for neurological conditions. Exclusions included those unwilling to participate or with severe cognitive impairments. Data were gathered using a validated self-administered questionnaire over four weeks. Pre-test scores mean 15.61 showed significant improvement post-intervention mean 18.80 P lt 0.05 highlighting the importance of educational programs to enhance knowledge in this group.Results Pre-test results revealed a mean knowledge score of 15.61 SD plusmn 3.86 which improved to 18.80 SD plusmn 3.85 post-intervention. Before the intervention 76.7 46 respondents had average knowledge 15 9 had good knowledge and 8.3 5 had poor knowledge. Post-intervention 68.3 41 displayed average knowledge while 31.7 19 showed good knowledge. A paired t-test indicated a statistically significant improvement in scores P lt 0.05 t 10.11.Conclusion The study revealed a significant improvement in knowledge about cognitive impairment and its management after implementing structured compensatory techniques emphasizing the importance of educational programs for patients with neurological disorders.